Overcoming the Design Challenge in 3D Biomimetic Hybrid Scaffolds for Bone and Osteochondral Regeneration by Factorial Design - Dellaquila, Alessandra; Campodoni, Elisabetta; Tampieri, Anna; Sandri, Monica (Frontiers in Bioengineering and Biotechnology, 2020)
The design and fabrication of hybrid constructs for tissue engineering is currently limited by lack of robustness of processes, which inevitably affects the biomaterial structural properties. The application of statistical approaches as design of experiment (DoE) represents a valuable tool to design and optimize engineered devices for regenerative medicine. In the present study, DoE was used to investigate the biofabrication of hybrid hydroxyapatite (HA)/collagen scaffolds for bone regeneration and their integration in a more complex multilayer osteochondral device. The scaffolds were synthesized via a bioinspired process that enabled the HA nano-crystals to nucleate on the collagen self-assembling fibers, eventually cross-linked via ribose glycation to modulate Young’s modulus and degradation rate in physiological environment. To study the complexity of the process, three independent parameters were selected as key variables in the fabrication: hydrogel concentration, HA/collagen ratio and cross-linking degree. Their value was tuned during the synthesis according to a full factorial DoE approach and the scaffold performances were tested by evaluating porosity, swelling ratio, degradation and mechanical behavior as output responses. The experimental data were subsequently used to build a statistical model able to define how the variation in the fabrication parameters influenced the scaffold performances. Moreover, physicochemical characterization of the constructs was conducted by TGA, ICP, FT-IR spectroscopy and XRD analysis to assess their biomimicry. Results revealed the significant interaction that occurs between HA content and collagen cross-linking in determining porosity, swelling and mechanical properties of the scaffolds. The combined effect of hydrogel concentration and mineral phase played a key role on porosity and swelling while degradation resulted to be mainly affected by HA loading and ribose glycation. The DoE model enabled a precise understanding of the effect of input variables and their interactions on scaffold properties. The model was then used to simulate the input parameters for the synthesis of scaffolds with graded mineralization rate with the final goal of fabricating constructs able to mimic the whole cartilage-bone interface. This work proved that experimental design applied to complex biofabrication processes represents an effective and reliable way to design hybrid constructs with standardized and tunable properties for osteochondral tissue engineering.